The determination of standard metabolic rate in fishes - Chabot, D.; Steffensen, J. F.; Farrell, A. P. (Journal of fish biology, 2016)
This review and data analysis outline how fish biologists should most reliably estimate the minimal amount of oxygen needed by a fish to support its aerobic metabolic rate (termed standard metabolic rate; SMR). By reviewing key literature, it explains the theory, terminology and challenges underlying SMR measurements in fishes, which are almost always made using respirometry (which measures oxygen uptake, ṀO2). Then, the practical difficulties of measuring SMR when activity of the fish is not quantitatively evaluated are comprehensively explored using 85 examples of ṀO2 data from different fishes and one crustacean, an analysis that goes well beyond any previous attempt. The main objective was to compare eight methods to estimate SMR. The methods were: average of the lowest 10 values (low10) and average of the 10% lowest ṀO2 values, after removing the five lowest ones as outliers (low10%), mean of the lowest normal distribution (MLND) and quantiles that assign from 10 to 30% of the data below SMR (q0·1, q0·15, q0·2, q0·25 and q0·3). The eight methods yielded significantly different SMR estimates, as expected. While the differences were small when the variability was low amongst the ṀO2 values, they were important (>20%) for several cases. The degree of agreement between the methods was related to the c.v. of the observations that were classified into the lowest normal distribution, the c.v. MLND (C.V.MLND). When this indicator was low (≤5·4), it was advantageous to use the MLND, otherwise, one of the q0·2 or q0·25 should be used. The second objective was to assess if the data recorded during the initial recovery period in the respirometer should be included or excluded, and the recommendation is to exclude them. The final objective was to determine the minimal duration of experiments aiming to estimate SMR. The results show that 12 h is insufficient but 24 h is adequate. A list of basic recommendations for practitioners who use respirometry to measure SMR in fishes is provided.